Answer:
g(-1) = -3
Step-by-step explanation:
g(-1) is the y value of the graph when x = -1
when x=-1 y=-3
g(-1) = -3
Answer:
15b + 30
Step-by-step explanation:
By expansion (6 x 2.5b) + (6 x 5)
= 15b + 30
F(x) = 3x^32 + 8x^2 -22x +43
The ends of all the polynomials with even degree behave like quadratic functions.
Given the the coefficient of x^32 is positive, the function opens upwards. Then the two ends go up.
Here, x - 2y = 14
x = 14 + 2y
Now, substitute this value into first equation,
4x + 6y = 0
4(14 + 2y) + 6y = 0
56 + 8y + 6y = 0
14y = -56
y = -56/14
y = -4
Substitute it into second equation,
x = 14 + 2(-4)
x = 14 - 8
x = 6
In short, Your Answer would be: (6, -4)
Hope this helps!
Answer:
option A.. 10 days
Step-by-step explanation:
option is 10 days is the correct answer
in one day he eats = 1and1/5 cups = 6/5 cups
one cup last for = 5/6 day
12 cups last for days = 12× 5/6 = 2× 5 = 10 days
so correct answer is 10 days ... option A
plz mark my answer as brainlist plzzzz vote me.. also Hope <u>it</u><u> </u><u>will</u><u> be</u><u> helpful</u><u> for</u><u> you</u>